The Effect of Virgin Coconut Oil (VCO) with Lotion On The Skin Moisture among Uremic Patients Undergoing Hemodialysis in Hospital Binjai City, Indonesia - Siti Saodah; Imam Budi Putra; Cholina Trisa S (Alta Dharma Publisher, 2020)
Chronic kidney failure is a public health problem throughout the world, and the number of sufferers is increasing. Chronic kidney failure can cause clinical symptoms in various body systems, one of which is a disorder in the skin that becomes dry (uremic). This study aimed to examine the effect of Virgin Coconut Oil (VCO) on the skin moisture among uremic patients undergoing hemodialysis. This type of research is a quasi-experiment with pre-test and post-test equivalent control group. The study was conducted at the Regional General Hospital, Dr. RM. Djoelham Binjai. The study population was 80 people, divided into 2 sample groups of 40 people each. The results showed that there was a significant effect of skin moisture on the intervention group before and after being given Virgin Coconut Oil, p = 0.000<0.05; There was a significant effect of skin moisture in the control group before and after lotion (post-test), p = 0.000<0.05. There is no need for special emulsions such as VCO to moisturize the skin in uremic patients undergoing hemodialysis because using ordinary lotions can moisturize the skin. It must be used regularly, twice a day after bathing. The lotion used must also be a lotion that does not contain mercury and chemicals that can harm the skin. To increase the skin's moisture becomes normal, giving lotion is better than VCO because by providing lotion, more skin becomes normal, while using VCO, the skin becomes more oily. It is recommended to health workers (doctors, nurses) to practice correctly and appropriately how to administer Virgin Coconut Oil (VCO) to uremic patients undergoing hemodialysis to be done at home